Anak krakatau mountain (AKM) causes a rare tsunami phenomenon: impact around the Sunda strait, Indonesia. Issue 1 (April 2021) - Sabara, Z; Umam, R; Prianto, K; Junaidi, R; Rahmat, A
Abstract: At the end of 2018, the rare tsunami phenomenon had been occurring at Sunda strait, Indonesia. This tsunami happened without feeling a huge earthquake, so many people did not know if there was a tsunami. Tsunamis occur at night and cause casualties, missing people, and damage around the Sunda Strait (Banten and Lampung). Previously, the observation of the activities of Anak Krakatau Mountain had been carried out intensively. Data collection is done from various sources. A literature study was also conducted to strengthen existing observations. From observational data open source obtained from the Badan Meteorologi Klimatologi dan Geofisika (BMKG) Indonesia, it was noted that earthquake activity by tectonic plates began in April 2018, while the intensity of the earthquake caused by increased activity of Anak Krakatau Mountain (AKM) began in June 2018. Eruptions and Tsunamis occurred on December 22, 2018. Although the alleged cause of the rare tsunami phenomenon has not been ascertained, the truth, from observations of satellite images and focus group discussions (FGD) from various society elements. Temporary allegations, the cause of the rare tsunami phenomenon is the AKM eruption, which makes the southwestern region of AKM island landslide of | 64 hectares to a layer below sea level. The impact that occurred after the tsunami has been reported by conducting surveys directly to locations on several beaches of Banten and Lampung. Damage that occurred around Banten and Lampung's coast was caused by houses very close to the coastline. Whereas in other areas that did not experience severe damage due to 2 factors, there are small islands that block the tsunami wave and the presence of mangrove vegetation around the Sunda strait.